In the Wolves' Den: : Brazil, Africa, and Germany in the Speeches of Baron of Jaurú During the Berlin Conference (1884-1885) (TEL Tempo, Espaço e Linguagem, 2025)
Article seeks to analyze the trajectory of César Sauvan Vianna de Lima (1824-1897), the Baron of Jaurú, and the way he describes the Berlin Conference between 1884 and 1885 and the evolution of European imperialism on the African continent. Through critical analysis of the diplomatic documents written by him, we seek to understand the events that preceded the conference, its development and the effects of his decisions on both the African continent and Brazil at the end of the Second Reign. Its importance lies in being a section that allows us to understand the gradual process of Brazilian support for the European colonial cause.